Growth of Hierarchically 3D Silver–Silica Hybrid Nanostructures by Metastable State Assisted Atomic Layer Deposition (MS‐ALD). Issue 7 (18th May 2017) - Ziegler, Mario; Yüksel, Sezin; Goerke, Sebastian; Weber, Karina; Cialla‐May, Dana; Popp, Jürgen; Pollok, Kilian; Wang, Dong; Langenhorst, Falko; Hübner, Uwe; Schaaf, Peter; Meyer, Hans‐Georg
Abstract : A novel fabrication strategy is introduced for the synthesis of 3D silver–silica hybrid nanostructures by employing the plasma‐enhanced atomic layer deposition (PE‐ALD) on the templated substrates with enzymatically generated silver nanoparticles (EGNPs). Comparing with the conventional PE‐ALD process for the silica deposition (by using the precursors of tri‐dimethyl‐amino‐silane (TDMAS) and oxygen plasma), here the EGNPs play a key role for the formation of 3D hierarchical structures. During the oxygen plasma step, a metastable silver oxide surface is formed, and then thermally decomposes and releases excess oxygen during the next TDMAS step. A side reaction for the deposition of silica occurs with the excess released oxygen. The formation of the metastable silver oxide and its decomposition repeat cyclically during the PE‐ALD process, thereby, the side reaction is going on progressively, and finally, the 3D silver–silica hybrid nanostructures are formed with this novel strategy of metastable state assisted atomic layer deposition. Various 3D silver–silica composite nanostructures, such as nanosponges and nanoflowers, can be fabricated easily by tuning the PE‐ALD parameters. With each additional ALD cycle, the silver particle size decreases which also further reduces side reactions. The observed growth‐effect thus seems to be limited by the amount of silver used. Abstract : A novel technique called "metastable state assisted atomic layer deposition" (MS‐ALD) is used to fabricate hierarchically 3D silver–silica hybrid nanostructures. The substrate switches between two phases within the deposition conditions of the MS‐ALD process and causes additional side reactions. The morphology of the structures can be adjusted by changing the MS‐ALD parameters.